Pruritus in cancer patients as a polyetiological symptom - Anna V. Michenko; Andrey N. Lvov; Larisa S. Kruglova; Dmitry V. Romanov; Ekaterina A. Kuzma (ZAO "Consilium Medicum", 2022)
Pruritus is one of the subjective sensations that significantly reduces the quality of life of patients. In patients with malignancies, itch can be caused by different universal or specific pathophysiological factors. This article discusses disorders that cause pruritus in cancer patients: the tumor growth on its own; pathophysiological changes associated with a number of malignancies, paraneoplastic itch, anticancer therapy, concomitant dermatoses, systemic diseases, psychosomatic disorders. Known or proposed mechanisms of the development of pruritus are presented for each of the mentioned provoking factors, and methods of treatment are described, according to the etiological factor. At the end of the article, universal methods for the correction of itching are presented, applicable in cancer patients, regardless of the pruritogenic factor. Special attention is paid to the correction of xerosis as a universal cause of itching in oncological patients.